Market Anticipation of Fed Policy Changes and the Term Structure of Interest Rates - Heidari, Massoud; Wu, Liuren (Review of Finance, 2010)
Abstract The Federal Reserve adjusts the federal funds target rate discretely, causing discontinuity in short-term interest rates. Unlike Poisson jumps, these adjustments are well anticipated by the market. We propose a term structure model that incorporates an anticipated jump component with known arrival times but random jump size. We find that doing so improves the model performance in capturing the term structure behavior. The mean jump sizes extracted from the term structure match the realized target rate changes well. Specification analysis indicates that the jump sizes show strong serial dependence and dependence on the interest-rate factors.